Municipal improvements and sanitary issues in towns in West Belarus area (1919–1939) - Aleksandr Darkovich (Historia provinciae: журнал региональной истории, 2017)
The article deals with the sanitary issues in West Belarus area during the inter-war period, as well as state and municipal governments’ efforts to improve the urban amenities. Financial difficulties of local authorities, underestimation of sanitary issues by the municipal officials, neglecting hygiene standards by the local people were among the main factors that prevented them from overcoming the critically low level of hygiene and sanitation. These are analyzed based on the archival materials.